2022
DOI: 10.3390/toxics10100566
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Metabolism of a Defined Pesticide Mixture through Multiple In Vitro Liver Models

Abstract: The evaluation of exposure to multiple contaminants in a mixture presents a number of challenges. For example, the characterization of chemical metabolism in a mixture setting remains a research area with critical knowledge gaps. Studies of chemical metabolism typically utilize suspension cultures of primary human hepatocytes; however, this model is not suitable for studies of more extended exposures and donor-to-donor variability in a metabolic capacity is unavoidable. To address this issue, we utilized sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
(103 reference statements)
0
5
0
Order By: Relevance
“… 58 Although the opportunities are many, the challenges are also formidable, including the cost, complexity, and low throughput of most of the available models. 38 , 59 , 60 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 58 Although the opportunities are many, the challenges are also formidable, including the cost, complexity, and low throughput of most of the available models. 38 , 59 , 60 …”
Section: Discussionmentioning
confidence: 99%
“…These models also improved our ability to collect and interpret pharmacokinetic data. 35 38 One liver model that showed great potential for in vitro metabolism studies is a micropatterned coculture (MPCC) system. 39 The MPCC platform has been shown to maintain the viability and metabolic activity of hepatocytes from rodents and humans for several weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The collected media was processed using high-performance liquid chromatography tandem mass spectrometry (HPLC-MS/MS) to determine the concentration of both the remaining parent compound (MDZ) and metabolites formed (1 -OH MDZ and 1 -OH MDZ glucuronide). We also tested the metabolism of equimolar mixtures (1 or 5 µM) of 20 pesticides that were previously used to evaluate the metabolic competence of different in vitro liver models [44]. Cells were treated on day 6 of culture, and media were collected for analysis 48 h thereafter.…”
Section: Overall Experimental Designmentioning
confidence: 99%
“…We also examined the metabolism of a mixture of 20 pesticides from different chemical classes and of different hydrophobicity with the HU8373 PHH mono-culture condition in the PhysioMimix LC12 and compared this to the published results of experiments with iHeps suspensions, 2D cultures, and OrganoPlate ® 2-lane 96 experiments [44]. We examined metabolism in a mixture setting because previous studies using suspensions of PHHs showed that hepatocyte metabolic clearance was slower under mixture conditions when compared to the individual incubations with these pesticides [47].…”
Section: Comparison Of Drug and Chemical Metabolism Among Cell Types ...mentioning
confidence: 99%
“…Combining metabolomics with in vitro experiments has the advantage of substituting animal testing and enabling a rapid identification of the toxicological properties of new compounds [ 26 , 27 ]. In particular, hepatic in vitro studies are widely conducted to evaluate the metabolic mechanisms related to toxicity [ 28 ] because the human hepatoma cell line maintains the activity of various enzymes that play an important role in activation and detoxification [ 29 ]. In a nutshell, in vitro metabolomics of hepatic cells have the potential to explain the effect of exposure to toxic substances [ 26 , 30 ].…”
Section: Introductionmentioning
confidence: 99%